Halogenation of diphosphane dichalcogenides. (1st December 2016) - Upmann, Daniel; Jones, Peter G.
GRAPHICAL ABSTRACT: ABSTRACT: Products of the reactions between dppmSe2 or dppeSe2 with elemental bromine or iodine have been characterized by X-ray diffraction.